2010
DOI: 10.1515/bc.2010.020
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in CHO cells stably transfected with domain-selective forms of murine ACE

Abstract: Membrane-bound human angiotensin-converting enzyme (ACE) has been reported to initiate intracellular signaling after interaction with substrates or inhibitors. Somatic ACE is known to contain two distinct, extracellular catalytic centers. We analyzed the signal transduction mechanisms in cells transfected with different forms of murine ACE (mACE) and investigated whether the two domains are similarly involved in these processes. For this purpose, CHO cells were stably transfected with mACE or with its domain-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…Moreover, we could demonstrate that these effects are additive, different from the results shown by Sun et al, 18 who 22,23 Ang II may also be equally effective at both sites. However, the capacity of binding to the enzyme is not the sole property of a molecule influencing its ability to activate ACE.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Moreover, we could demonstrate that these effects are additive, different from the results shown by Sun et al, 18 who 22,23 Ang II may also be equally effective at both sites. However, the capacity of binding to the enzyme is not the sole property of a molecule influencing its ability to activate ACE.…”
Section: Discussioncontrasting
confidence: 97%
“…The activation of the c-Jun N-terminal kinase in CHO cells was shown to be promoted not only exclusively by the active C-domain of human ACE 17 but also by the N-domain in murine ACE. 18 We could show that the calcium signaling promoted by Ang II in these cells is produced to a similar extent by both domains of human ACE, and the interaction of these compounds with a single catalytic domain is obviously sufficient to induce the signaling effect.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Literature data showed that some ACE substrates or inhibitors triggered an increase of casein kinase 2 (CK2) activity, leading to ACE Ser1270 residue phosphorylation with subsequent activation of JNK, as well as the accumulation of phosphorylated c-Jun in the nuclei of endothelial cells (37). Similar results were also obtained for murine ACE (61). It also has been demonstrated that ANG II is able to interact with ACE in Chinese hamster ovary (CHO) cells transfected with this enzyme and melanoma cells, triggering calcium signaling and promoting an increase of reactive oxygen species by the activation of the enzyme (24).…”
Section: Introductionsupporting
confidence: 58%
“…As described above, several studies have shown that binding of ACE inhibitors to the enzyme triggers signaling pathway activation (3,24,37,61). However, to date, none of these studies were conducted with a sulfhydryl group containinginhibitor such as captopril, and none of them have investigated ERK1/2 phosphorylation signaling pathway either.…”
Section: Introductionmentioning
confidence: 99%